Outbreak Investigation and Control of Coronavirus Disease 2019 in Entertainment Venues along Bangla Road, Phuket Province, Thailand, March–April 2020 - Naraart, Panuwat; Wareewanit, Kalita; Choolue, Thapanee; Leng-aee, Wipawadee; Kamsamarn, Samarnsri; Na Nakorn, Natpimon; Sittibun, Walailuck; Siriphon, Kochrada; Chaivisit, Pawit; Bohna, Narasak; Yodngeon, Bulakon; Swangpun, Kusuma; et al. (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2021)
On 22 Mar 2020, the investigation team was notified by the Phuket Provincial Health Office that there was an outbreak of coronavirus disease 2019 linked to entertainment venues on Bangla Road, Phuket Province. An outbreak investigation was conducted to verify, describe, and control the outbreak. A descriptive study was conducted by gathering epidemiological and clinical data from cases and an environmental study was conducted at the entertainment venues on Bangla Road. There were 63 confirmed cases linked to the entertainment venues. Most of the cases were Thai female employees. The median age was 32 years, and waitress and security staff were the most common occupations. The majority of cases were symptomatic with mild level of severity. The clinical manifestations were sore throat, cough and fever. Factors associated with being a case were occupational risk of infection, that is, having contact with a large number of tourists. The entertainment venues where cases were found were mostly air-conditioned closed indoor settings. This event might have originated from imported cases followed by local transmission. Therefore, employees and customers should be screened before working at or entering entertainment venues.